'Mad', bad or Muslim? The UK's Vulnerability Support Hubs and the nexus of mental health, counterterrorism and racism. (20th December 2021) - Aked, Hil
Abstract: The UK government's 'Prevent' counter‐extremism policy was placed on a statutory footing in 2015, requiring specified authorities including NHS providers by law to work to 'prevent people being drawn into terrorism', leading to calls for a boycott on ethical grounds. Since 2016, mental health professionals have been embedded within counterterrorism police units in 'Vulnerability Support Hubs', to assist in the management of individuals referred to Prevent perceived to have vulnerabilities related to mental health. Drawing on data obtained through Freedom of Information requests, this paper examines these hubs in the context of Prevent's racial politics. It examines the pseudo‐scientific concept of radicalization through the lens of racialization theory and explores the whitewashing and colourblindness endemic to most research and practice at the nexus of counterterrorism and mental health. Four ethical issues arising from the hubs are highlighted: (a) the securitization of care, including the way counterterrorism concerns appear to influence medical treatment regimes; (b) harm, including potential criminalization; (c) the erosion of patient agency and confidentiality; and (d) the pathologization of political dissent. It is argued that due to the UK's status as a leading innovator in the field of counter‐radicalization, all of these highly racialized phenomena hold wider relevance and augur a troubling direction of travel for counterterrorism's turn towards mental health.